Epidermal Growth Factor Receptor Mutation-Positive Non–Small-Cell Lung Cancer in the Real-World Setting in Central Europe. Issue 9 (September 2015) - Ramlau, Rodryg; Cufer, Tanja; Berzinec, Peter; Dziadziuszko, Rafal; Olszewski, Włodzimierz; Popper, Helmut; Bajcic, Paolo; Dušek, Ladislav; Zbozinkova, Zuzana; Pirker, Robert
<x xml:space="preserve">Abstract</x> The ImplementatioN of perSonalized medicine In NSCLC in Central Europe: EGFR testing, Histopathology, and clinical feaTures (INSIGHT) observational study assessed both implementation of epidermal growth factor receptor (EGFR) mutation testing and treatment of patients with advanced EGFR mutation-positive non–small-cell lung cancer (NSCLC) in a real-world setting in Central Europe. A total of 1785 patients from 14 cancer centers of six Central European countries were enrolled. EGFR mutations were detected in tumors of 13.8% of the patients. More than 70% of patients with advanced EGFR mutation-positive NSCLC received EGFR tyrosine kinase inhibitors as first-line therapy. The INSIGHT study demonstrated the establishment of EGFR mutation testing, a mutation rate consistent with other Caucasian patients populations, and adherence to current guidelines regarding treatment of patients with EGFR mutation-positive tumors in Central Europe.